The perception of professors of Management Course of a Northeast Federal University on the selection processes for professors - Almeida Neto, Francisco Sergio de; Siqueira, Elisabete Stradiotto; Binotto, Erlaine (Revista de Administração da UFSM, 2017)
This paper has aimed to analyze the perception of the administration course professors of a federal university at northeast that take part of selection processes have about the selection process which involved as applicants. The study consisted of exploratory research with qualitative complemented by quantitative data. This university is part of the REUNI program was chosen as analysis considering the expansion process that have been occurring on the last years. Took part in this survey 88% of the professors from administration course of the university. The data show that although in the university, teaching, research and extension compose the tripod that supports the academic making, this can not be perceived in the conceiving of the professors surveyed as an important value in the selection process. It is concluded that the board of assessment is the main target of criticism of the candidates. It needs more transparency, from the choice of the board to their evaluation criteria.<pre style="text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"><span style="font-size: 12pt; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">This paper has aimed to analyze the perception of the administration course professors of a federal university at northeast that take part of selection processes have about the selection process which involved as applicants. The study consisted of exploratory research with qualitative complemented by quantitative data. This university is part of the REUNI program was chosen as analysis considering the expansion process that have been occurring on the last years. Took part in this survey 88% of the professors from administration course of the university. The data show that although in the university, teaching, research and extension compose the tripod that supports the academic making, this can not be perceived in the conceiving of the professors surveyed as an important value in the selection process. It is concluded that the board of assessment is the main target of criticism of the candidates. It needs more transparency, from the choice of the board to their evaluation criteria.